Índice de astrócitos gemistocíticos e imuno-expressão da proteína p53 em astrocitomas, grau II e III OMS - Martins, Dely Cristina [UNIFESP] (2001)
Twenty-two patients with astrocytomas, grade II or III WHO, were studied from 1990 to 1998. In all cases, histopathology showed that the astrocytomas had a gemistocytic component. The aims of this study were to establish the fraction of gemistocytic astrocytes, to investigate p53 protein immunoexpression and to evaluate correlations between these two parameters with the tumour outcome. Tumor cells were quantified at high-power magnification (x400). At least 1000 neoplastic cells (small neoplastic astrocytes plus gemistocytes) were counted in each specimen. The percentage of gemistocytes was defined as the gemistocytic index. Nuclear expression of p53 protein was evaluated in neoplastic astrocytes and gemistocytes. Both the frequency (7/22) as well the p53 immunoexpression indices in gemistocytes, regardless of the grade of the astrocytomas, were inferior from those reported in the literature. No correlation was found between the gemistocytic indices and the p53 immunoexpression.